HIV serology using fourth-generation ELISA techniques - Aline Daniele Schuster (Universidade de Santa Cruz do Sul, 2013)
Backgound and Objectives: Since its introduction in the mid-1980s, HIV testing has gradually improved in terms of sensitivity and specificity. A study was carried out to assess the techniques used in a hemotherapy center for human immunodeficiency virus (HIV) identification using two 4th-generation enzyme-linked immunosorbent assay (ELISA) methods. Methods: descriptive and retrospective study of 4th-generation ELISA techniques, which analyzed all the results generated from blood samples obtained from donors aged 16 to 68 years, according to current legislation, who attended a regional blood bank from November 2010 to October 2011. Results: Of 8,475 samples collected through blood donation, 06 were positive or inconclusive at the screening tests and were then analyzed through Western Blot confirmatory test, which confirmed one of them was reagent for the virus. Conclusion: Several factors influence positive results of screening samples, such as type of test used, the immunological window, use of antiretroviral drugs, and personal biological factors of infected individuals. The effectiveness of HIV screening tests should be determined and the methodology improved, so that it can establish with certainty the existence or not of contamination of blood products that will be used later. More research is needed to constantly improve the screening tests and give adequate emphasis to factors that have shown to alter results.